CANVA-BASED INTERACTIVE LEARNING MEDIA TRAINING TO IMPROVE TEACHER LITERACY - Priska, Melania; Wao, Yosephina P; Jariyah, Ainun; Wae, Veronika P S M; Fatima, Noviana Deam (LPPM Universitas Flores, 2025)
The Canva-based interactive learning media training aimed to improve the literacy skills and abilities of teachers at SMPN 2 Ende Selatan. The training was attended by teachers and students as participants, as well as lecturers and students from the Biology Education study program at the University of Flores who served as resource persons. The training consisted of two stages: preparation and implementation. The results showed that the Canva platform was effective in improving the literacy skills and abilities of teachers at SMPN 2 Ende Selatan. Using the Canva platform to create interactive and non-monotonous learning media can create a more visual, creative, and engaging learning process for students, thereby increasing their motivation to learn.